Implementasi Website Manajemen Sekolah di Sekolah Dasar Menggunakan Metode Waterfall - Ismail, Ahmad Hafizh; Abdul Rohman (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
This research discusses the implementation of a website-based school management system at SD Negeri Candirejo 02 using the waterfall method. This system is designed to manage academic data digitally and replace manual processes, with features such as managing teacher data, student data, schedules, classes, and teacher attendance. Research data was collected through observation and interviews to identify needs and problems. As a result, this school management website supports the effectiveness of academic data management and can provide easier access to information for teachers and students. And from the test results using black-box shows that the system functions as expected.